The effect of high-intensity interval training in swimming on alpha-synuclein (α-Syn) and cAMP-responsive element-binding protein (CREB) gene expression in rats with Parkinson’s disease - Mehdi Javidi; Mehrzad Moghadasi; Mohammdamin Edalatmanesh; Mehdi Noora (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Parkinson's disease is characterized by an increase in alpha-synuclein (α-Syn) and a decrease in cAMP-responsive element-binding protein (CREB) levels in the brain. This study aimed at investigating the effects of a period of high-intensity interval training in swimming on α-Syn and CREB gene expression in rats with Parkinson's disease. Methods: In this experimental study, 21 male Wistar rats aged 8 to 10 weeks were selected. Fourteen rats were induced with Parkinson's disease through intraperitoneal injection of reserpine and randomly divided into patient and training groups. Additionally, seven healthy rats served as the control group. Rats in the training group underwent 20 sets of 30-second swims with 30-second rest intervals over a period of 6 weeks. α-Syn and CREB gene expression levels were measured using Real-Time PCR in blood samples collected 48 hours after the final training session in all groups. Results: The patient group exhibited significantly higher α-Syn gene expression compared to both the control group and the training group (P=0.001 and P=0.002, respectively). However, no significant difference was observed between the training and control groups (P=0.2). Additionally, CREB gene expression was significantly lower in the patient group compared to both the control group and the training group (P=0.006 and P=0.003, respectively), with no significant difference between the training and control groups (P=0.6). Conclusion: High-intensity interval training in swimming may reduce α-Syn expression and increase CREB levels, potentially contributing to the survival of dopamine neurons and improvement in Parkinson's disease symptoms. Further research in this area is warranted to validate these findings.